ABDOMINAL AORTIC CALCIFICATION IN ALDOSTERONE PRODUCING ADENOMA AND IDIOPATHIC HYPERALDOSTERONISM. (April 2021) - Shibayama, Yui; Wada, Norio; Baba, Shuhei; Obara, Shinji; Sakai, Hidetsugu; Usubuchi, Hiroaki; Terae, Satoshi; Kameda, Hiraku; Nakamura, Akinobu; Atsumi, Tatsuya
Abstract : Objective: Aldosterone promotes vascular calcification, which leads to atherosclerosis and eventually cardiovascular disease via enhancing vascular osteoinductive signaling, oxidative stress, inflammation and apoptosis. As an independent prediction of coronary artery disease (CAD), abdominal aortic calcification has been useful as well as coronary artery calcification. It has been shown that patients with aldosterone producing adenoma (APA) have higher rate of CAD comparing patients with idiopathic hyperaldosteronism (IHA) at the diagnosis of primary aldosteronism (PA). However, no data have shown whether the degree of abdominal aortic calcification is different between APA and IHA. We aimed to clarify the degree of abdominal aortic calcification in each subtype of PA. Design and method: This retrospective observational study comprised 170 patients diagnosed with PA. We divided participants into APA (n = 48) and IHA (n = 132), according to the results of adrenal venous sampling (AVS) and pathological findings. Aortic calcification index (ACI) was evaluated by unenhanced abdominal computed tomography, focusing around the left renal artery and scanning 10 times at 10-mm intervals. Results: Age was not different between the two subtypes (p = 0.47). Duration of hypertension and plasma aldosterone concentration were significantly higher in APA than IHA (p < 0.001, p < 0.001, respectively). Neither smoking ratio, HbA1c, LDL-cholesterol, nor eGFR was different between the two subtypes (p = 0.86, p = 0.49, p = 0.20, p = 0.47, respectively). The percentage of patients with ACI > 1 was significantly higher in APA than IHA (APA vs. IHA; 17/48 (35.4%) vs. 25/132 (18.9%), p = 0.03). In patients with ACI > 1, ACI was correlated with duration of hypertension in both subtypes of PA (APA; r = 0.62, p = 0.01, IHA; r = 0.49, p = 0.02). Conclusions: Abdominal aortic calcification was progressed in APA than IHA. This result was concordant with higher rate of CAD in APA than IHA. In both subtypes of PA, patients with longer duration of hypertension tended to coexist abdominal aortic calcification, demonstrating an importance of early diagnosis and treatment before developing to aortic calcification in either subtype of PA.